Microbiological assessement of spaghetti from selected restaurants in Iloilo City - Morales, Ivony Gador (2007.)
Microbilogical analyses, namely, coliform count and detection of specific pathogens (Salomonella and Staphylococcus aureus) were conducted on the spaghetti samples from the three selected food establishmnets (identified as A, B and C) in Iloilo City.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Pathogens; Spaghetti